# 1 FUNCTIONS

1.0 RELATIONS Notes : (i) (ii) (iii)

Four types of relations : one-to-one, many-to-one, one-to-many and many-to-many. Three ways to represent relations : arrowed diagram, set of ordered pairs and graph. The arrow diagram representation is of the form below : P :Domain P Q : Codomain Q A : Domain A 1_ 3 B : Codomain B

_4

a

_5 _
6

•b

a is the object

b is the image

Set { 4, 6 } is the RANGE for the mapping from A to B The relation from A into B above can also be written as set of ordered pairs {(1, 4), (3, 6) } 4 is the image of 1 ; The Object of 6 is 3.

In the above relation, b is the imej of a ; a is the object of b.

(iv)

Set of ordered pairs of a relation takes the form of { (a , b), (c , d), ….. }

EXAMPLE
1.
P = { 1, 2, 3} Q = {2, 4, 6, 7, 10}

QUESTION
1.
P = { 2, 4, 6} Q = {2, 3, 6, 7, 10}

A relation from P into Q is defined by the set of ordered pairs { (1, 4), (1, 6), (2, 6), (3, 7) }. State (a) (b) (c) (d) (e) (f)

A relation from P into Q is defined by the set of ordered pairs { (2, 2), (4, 2), (6, 7) }. State (a) (b) (c) (d) (e) (f)

the image of 1, the object of 4, the domain, the codomain, the range, the type of relation

Ans: 4 and 6 Ans: 1 Ans: { 1, 2, 3 } Ans: {2,4,6,7,10} Ans: { 4, 6, 7 } Ans: many-to-many

the image of 4, the objects of 2, the domain, the codomain, the range, the type of relation

Ans: Ans: Ans: Ans: Ans: Ans:

Functions

1

1.1 FUNCTION NOTATIONS Notes: (i) A function is usually represented using letters in its lower case : f , g , h ….. (ii) Given the function f : x  2 x  1 , we usually write it in the form f(x) = 2x + 1 before answering any question. 1.2 FINDING THE VALUE OF FUNCTIONS [Mastery Exercise] f (a) represent (a) the value of f(x) when x = a . (b) the image of f when the object is a EXAMPLE 1. Given the function f : x  2 x 1 , find Answer : (i) f (3) (ii) f (-4) QUESTION 1. Given the function f : x  2 x  3 , find (i) f (2) Answer : (ii) f (-1)

f(x) = 2 x + 1 (i) f ( 3 ) = 2 (3 ) + 1 = 6+1 = 7 (ii) f (-2 ) = 2 (-2) + 1 = -4+1 = -3

f(x) = 2 x + 3 (i) f(3) = 2( ) + 3 = = (ii) f(-1) = 2 ( ) + 3 = =

2. Given the function g : x  x 2  3 , find (i) g(0) (ii) g(4) Answer : g (x) = x2 - 3 (i) g ( 0 ) = 02 - 3 = 0 - 3 = -3 (ii) g (4) = 42 - 3 = 16 – 3 = 13 3. Given the function h : x  find h (2). Jawapan :
6 h ( x)  3x  4 6 4 , x , 3x  4 3

2. Given the function g : x  x 2  5 , find (i) g(0) (ii) g(2) Answer : g (x) = x2 - 5

(i) g ( 0 ) = = = (ii) g (2) = = = 3. Given the function h : x  find h(3). Jawapan:
h ( x) 

9 3 , x , 2 2x  3

h(2) = = =

6 3(2)  4 6 2

h(3) =

3

Functions

2

find 3 4x (a) h (0) (b) h (1) (c) h ( 1 ) 2 (d) h(-3) (e) h ( 1 ) 4 Functions 3 . f ( x ) = 3x + 1 (a) f (0) (b) f (3) (c) f(-2) (d) f(4) (e) f(-3) (a) f ( 0 ) = 3 ( 0 ) + 1 = ANSWER 2 . find 1.2 FINDING THE VALUE OF FUNCTIONS [Reinforcement Exercises] QUESTION 1. Given the function h : x  6 . Given the function f : x  3 x  1 . (a) g (0) (b) g (2) (c) g (4) (d) g (-3) (e) g (-1) g(x) = x2 .3x (a) g (0) = 3.1. find 2. Given the function g : x  x 2  3x .

find the value of p if f(p) = g(p). Answer : 4. Answer : f (x) = 5 x + 3 5 x + 3 = -7 5x  x = . find the value of x if f(x) = -7. Given that g : x  x  2 . Answer : f (x) = 4 x – 3 4 x – 3 = 17 4x x = = 2. Given that f : x  5 x  3 . Given that f : x  4 x  3 . g(x) = 4x + 15 f(p) = 7p – 3.10 = -2 2. Answer : f(x) = 7x – 3. Given that f : x  7 x  3 . Given that g : x  3 x  2 . g : x  4 x  2 . Given that f : x  2 x 1 . g(y) = 2y + 4. [1] Note : Questions on functions usually involve solving linear / quadratic equations. find the value of x if f(x) = g(x). Given that f : x  3 x  7 . find the value of x if f(x) = 4. find the value of x if f(x) = 17. g : x  4 x  15 . Given that f : x  2 x 10 .3 PROBLEM OF FUNCTIONS INVOLVING SIMPLE EQUATIONS. g(p) = 4p + 15 f(p) = g(p) 7p – 3 = 4p + 15 3p p = 18 = 6 Functions 4 . Answer : f (x) = 2 x – 1 2x–1 = 5 2x  x = 6 = 3  QUESTION 1. find the value of x if f(x) = 5. find the value of y 3.3 Answer : g(x) = x + 2 g(y) = y + 2 y+2 = 2y–3 3+2 = 2y-y y = 5 4. EXAMPLE 1.1. Answer : 3. find the value of y if if g(y) = 2y .

A: g(x) g(p) 3p2 . QUESTION 5. g(x) = x – 7 2x – 10 = . find the values of x if f (x) = x2.6 = (3p+2) (p – 3) = p=  2 3 atau Functions 5 . = 3x2 – 6 = 3y2 . Given f : x  3 x  9 . p if g (p) = 7p. find the values of p if g(p) = .3x – 4 = 0 (x + 1) (x – 4) = 0 x = -1 or x = 4 7.6 3y2 – 12 (÷3) : y –4 2 g (y) = 45 . g : x  x  7 . 6.5p . Given that g : x  2 x 2  3 .6 7p 0 0 p=3 . Given that g : x  3 x 2  6 . Given that g : x  3 x 2  6 . find the values of x if f (x) = x2.10 . find the value of x if f(x) =  2 g(x) A: f(x) = 2x . Given that g : x  2 x 2  5 . A: f(x) = 3x + 4 x2 = 3x + 4 x2 .10 = . find the values of y if y if g (y) = 6 . find the values of 8. Given that f : x  2 x  8 . Given that f : x  3 x  4 . Given that f : x  2 x 10 .PROBLEMS OF FUNCTIONS INVOLVING SIMPLE EQUATIONS. find the value of x if f(x) =  3 g(x).6 = 6 = 0 = 0 (y + 2) (y – 2) = 0 y = -2 or y = 2 8.6 = = = 3x2 – 6 3p2 . [2] EXAMPLE 5. 3p2 – 7p . g : x  x  7 .2 (x – 7) 2x .2x + 14 4x x = 24 = 6 6. find the values of 7. A: g(x) g(y) 3y2 .

(b) the values of x if f(x) = x. g(x) = (a) the value of p if f(p) = -5 (b) the value of k if g(k) = 3k . Given the function f : x  3 x 2  12 .3 (c) the value of p if f(p) = g(p) (d) the value of x if f(x) = – g(x) (a) f(x) 2x – 5 2x x 2.PROBLEM OF FUNCTIONS INVOLVING SIMPLE EQUATIONS [Reinforcement Exercises] QUESTION 1. Given the functions f : x  3 x  4 and g : x  2 x . (c) the values of y if f(y) = g(y). Given the functions f : x  2 x  5 and g : x  x  2 . f (x) = . 3. (a) evaluate f 2 (-2).4 (c) the value of x if 2 f(x) = g(x) (d) the values of y jika f(y) = y2 3. g(x) = (a) the image of 3 that is mapped by f . g(x) = x + 2 = 7 = 7 = = (a) the value of x if f(x) = 7 (b) the value of y if g(y) = 2y . (b) solve the equation f(x) = 0. f (x) = (a) f (p) = -5 3p + 4 = -5 . (c) find the values of p if f(p) = 3p + 6. f (x) = (a) f 2(-2) = f f(-2) = f( = ) f(-2) = 3(-2)2 – 12 = 4. find 2. ANSWER f(x) = 2x – 5 . find 1. find 4. Given the functions f : x  x 2 and g : x  12  4 x . Functions 6 .

find gf(4). find fg(3). Given the functions f : x  x  3 and g : x  4 x  1 . find 4. g(x) = 2x g(3) = 2(3) = 6 fg(3) = f [ g(3) ] = f ( 6) = 3 (6) . we can first find fg(x) and then substitute x = a. EXAMPLE 1 : Given that f : x  3 x  4 and g : x  2 x . g(x) = x2. Given that f : x  2 x  9 and g : x  1  3 x .4 FINDING THE VALUE OF COMPOSITE FUNCTIONS [Mastery Exercises] Notes : To find the value of fg(a) given the functions f and g. EXAMPLE 2 : Given that f : x  3  2 x and g : x  x 2 . find f g(1) .1. We can also follow the EXAMPLES below. find (a) f g(1) (b) gf(1) (a) f g(0) (b) gf(0) Functions 7 . find gf(3). f(4) = 3 – 2(4) = 3–8 = -5 gf(4) = g (-5) = (-5)2 = 25 EXERCISES 1. 2. Given that f : x  2 x  1 and g : x  3 x . Given the functions f : x  3 x  7 and g : x  4  2 x . 3.4 = 14 Answer : f(x) = 3 – 2x .4 . Answer : f(x) = 3x .

Given that f : x  2 x  5 and g : x  5 x . Given that f : x  3 x  4 and g : x  5  2 x . 3. find (a) fg(-2) (b) gf(-2) (a) fg(-1) (b) gf(-1) 7. Given the functions f : x  2  x and g : x  1  4 x  3x 2 . Given that f : x  x  4 and g : x  2 x  1 . Given that f : x  2 x  3 and g : x  4 x . 4. Given the functions f : x  x  2 and g : x  2  3 x  x 2 . find gf(7) . find (a) fg(-1) (b) gf(-1) Functions 8 . find (a) fg(1) (b) gf(1) find (a) fg(0) (b) gf(0) 5 Given the functions f : x  3 x 2 1 and g : x  2  x .FINDING THE VALUE OF COMPOSITE FUNCTIONS [Reinforcement Exercises] 1. find 6 Given that f : x  3 x and g : x  2  x 2 . find (a) fg(1) (b) gf(1) 8. 2. find fg(2) .

Given that f : x  2 x  3 . Answer : f(x) = 3x . 8. find ff(0) .2 f(2) = 3(2) – 2 = 4 f2(2) = f [ f(2) ] = f ( 4) = 3 (4) – 2 = 10 EXAMPLE 2 : Given that g : x  3  4 x . find f 2(2) . Given that g : x  4 x . 2. 7. Given that g : x  2  5 x . evaluate g 2(3). Given that f : x  3 x  4 .1. 5. 4. Diberi f : x  2 x 2  4 x  3 . Given that f : x  3x 2  1 . find ff(1) . g 2 Notes : f 2(a) = ff (a) = f [ f (a) ] EXAMPLE 1 : Given that f : x  3 x  2 . Given that g : x  x  5 . find f 2(2). evaluate gg(-2). Nilaikan f 2(0) . evaluate gg(1). Functions 9 . Given that g : x  2 x  1 . evaluate gg(3) . Answer : g(x) = 3 – 4x g(1) = 3 – 4(1) = -1 gg(1) = g [g(1)] = g ( -1) = 3 – 4 (-1) = 3+4 = 7 EXERCISES 1. find g 2(1). 3.5 FINDING THE VALUE OF COMPOSITE FUNCTIONS f 2 . 6.

EXAMPLE 2 : Given g : x  5  4x . Given f : x  2x  3 . g(x) = thus (a) g (2) = thus (a) f(2) = 2(2) + 3 = (b) f(a) = (b) g(a) = (c) f(p) = (c) g(s) = (d) f(2k) = (d) g(3x) = (e) f(x2) = (e) g(x2) = (f) f(-x2 ) = (f) g (3+2x) = (g) f( .7 – 8x (c) f(p) = 3 p + 1 (d) f(2k) = 3 (2k) + 1 = 6k + 1 (e) f(2x) = 3 (2x) + 1 = 6x + 1 (f) f(x ) = 3 x + 1 2 2 EXERCISES 1. f(x) = 3x + 1 thus (a) f(2) = 3(2) + 1 = 7 (b) f(a) = 3a+1 thus g(x) = 5 – 4x (a) (b) (c) (d) (e) (f) g(2) = 5 – 4(2) = 5 – 8 = -3 g(a) = 5 – 4a g(p) = 5 – 4p g(3k) = 5 – 4(3k) = 5 – 12 k g(x2) = 5 – 4x2 g (3+2x) = 5 – 4 (3+2x) = 5 – 12 – 8x = . .6 BASIC EXERCISES BEFORE FINDING THE COMPOSITE FUNCTIONS [ 1 ] EXAMPLE 1 : Given f : x  3x  1 . f(x) = 2x + 3 2 Given g : x  2  4x .3x) = (g) g(2 – 4x) = Functions 10 .1.

f(x) = 4 – 2x thus (a) f(3) = 4 – 2 (3) = (b) f(-x) = thus (a) (b) (c) g(x) = g(-1) = g(2x) = g(x-2) = (c) f(2+x) = (d) f(3 -x) = (e) f(x2) (d) g(-3x) = g(x2) = = (e) (f) f(-x2 +2) = (f) g (1-2x) = 3. 2 Given g : x   2x  1 .3) = (e) g(x2) = (f) f(x2) = (f) g (1+2x) = Functions 11 . . f(x) = thus (a) f(10) = thus (a) g(x) = g(-1) = (b) f(3x) = (b) g(2x) = (c) f(2 . Given f : x  4  2x . Given f : x  1 x .x) = (c) g(x-1) = (d) f(4+x) = (d) g(-x) = (e) f(2x.BASIC EXERCISES BEFORE FINDING THE COMPOSITE FUNCTIONS [ 2 ] 1. 4 Given g : x  2( x  2) .

2. gf(x) = g[f(x)] = g (3 – 2x) = (3. find fg(x).4 . Given that f : x  3 x  4 and g : x  5  2 x . find (a) fg(x) (b) gf(x) (b) f g (b) gf Functions 12 .1. Answer : f(x) = 3x .7 FINDING COMPOSITE FUNCTIONS EXAMPLE 1 : Given that f : x  3 x  4 and g : x  2 x . find the composite function gf. find fg(x) .4 = 3 (2x) – 4 = 6x-4 OR gf(x) = g[f(x)] = [f(x)]2 = (3. g(x) = 2x fg(x) = f [ g(x) ] = f ( 2x) = 3 (2x) . g(x) = x2. Given that f : x  2 x  3 and g : x  4 x . 3. find the composite function gf . Given that f : x  2 x  5 and g : x  5 x . Given the functions f : x  x  4 and g : x  2 x  1 . EXERCISES 1.2x)2 EXAMPLE 2 : Given that f : x  3  2 x and g : x  x 2 .2x)2 thus gf : x  (3  2 x) 2 Answer: f(x) = 3 – 2x .4 = 6x – 4 OR fg(x) = f [ g(x) ] = 3 [g(x)] . find 4.

Given the functions f : x  x  2 and g : x  5  2 x . find the composite function gubahan (a) fg(x) (b) gf(x) (a) fg (b) gf Functions 13 . find the composite functions (a) fg(x) (b) gf(x) (a) fg (b) gf 3. find 4. Given that f : x  2  5 x and g : x  1  x 2 . Given that f : x  3 x and g : x  2  x 2 . Given the functions f : x  x  4 and g : x  1  3 x . Given that f : x  3  x and g : x   4 x  3 . Given the functions f : x  3 x  2 and g : x  2  2 x . find 2. find 6.REINFORCEMENT EXERCISES FOR FINDING COMPOSITE FUNCTIONS 1. find the composite functions (a) fg(x) (b) gf(x) (a) f g (b) gf 5.

Given that g : x  1  3 x . Given that f : x  3  4 x . 9.REINFORCEMENT EXERCISES FOR FINDING COMPOSITE FUNCTIONS [ f2 and g2 ] 1. Given that f : x  2  5 x . find g 2(x). f(x) = 3x + 2 f2(x) = f [f(x)] = f (3x + 2) = 3(3x+2) + 2 = 3. 8. find the function f 2. Given that f : x  3 x  2 . 6. Given that g : x   4 x  3 . or 3f(x) + 2 2. Given that h : x  2 . x2 Functions 14 . 5. find f 2(x). find the function f 2. Given that f : x  3 x . find f 2(x). find ff(x) . Given that g : x  1 x . find the function f 2. find gg(x) 4. Given that f : x  x  2 . find the function f 2. 2 10. Given that f : x  5 x . find the function g 2. 7.

If y = 3 + 5x . If y = 4x – 2 . If y = 3 – 6x .8 INVERSE FUNCTIONS Notes : 1. If f (x) = y. then x = f(y) EXAMPLE 1. If y = 4 – 5x . then x = Functions 15 . METHOD 1 METHOD 2 Given then f(x) = 2x – 3 f(y) = 2y – 3 f –1 ( 2y – 3 ) = y f –1 ( x ) = y y3 2 x3 2 Given f(x) = 2x – 3 . then x = 6. find f –1(x). Students must be skillful in changing the subject of a formula ! 2. then x = 4. Given that f(x) = 2x – 3 . then x = 3x – 2 = y 3x x = y+2 = y2 3 2.1. then x = 4x – 2 = y 4x x = = 3. If y = 10x – 4 . then f –1( 2x – 3 ) = x. then x = f –1(y) OR if f –1(x) = y. If y = 3x – 2 . f –1 ( y ) = x when y = 2x – 3 y + 3 = 2x x = f –1(y) =  f –1(x) = y3 2 x3 2 when x = 2y – 3 x + 3 = 2y y = x3 2  f –1 (x) = Students are advised to master only one of the methods ! DRILLING PRACTICES ON CHANGING SUBJECT OF A FORMULA [ 1 ] 1. then x = 5.

If y = 2x  5 . If y = 3x  2 . If y = 1 3x  2 . If y = x 1 4x  2 . then x = 3 x Functions 16 . If y = 4 – 1 x . then x = 10. If y = 2x . then x = 2 3. then x = 7. If y = 5 + 6x . then x = 4 x 9. If y = 2 . then x = 5.DRILLING PRACTICES ON CHANGING SUBJECT OF A FORMULA [ 2 ] 1. then x = 4 2x  5 = y 4 2. then x = 2 6. If y = 6x – 9 . then x = 8. If y = 6 + 3 x . then x = 5 2x – 5 = 4y 2x x = = 4.

2x  1 . 2. find g –1 . f –1( x ) = y when x = 4y – 6 x + 6 = 4y y=  f –1(x) = x6 4 x6 4 –1 EXAMPLE 2 : Given that f : x  f –1(x). Functions 17 . find f (x). find g–1. 2 x Given so then f(x) = f(y) = f –1( 2x  1 2 x 2y 1 2 y 2y 1 ) = y 2 y f –1( x ) = y when x = 2y 1 2 y x(2 . find Answer : Given so then f(x) = 4x – 6 f (y) = 4y – 6 f –1( 4y – 6 ) = y.DETERMINING THE INVERSE FUNCTION FROM A FUNCTION OF THE TYPE ONE-TO-ONE CORRESPONDENCE EXAMPLE 1 : Given that f(x) = 4x – 6 . x  2. x2 EXERCISES 1. Given that g : x  15 + 6x . Given that f : x  4 – 3x .y) = 2y + 1 2x – xy = 2y + 1 2x – 1 = 2y + xy 2x – 1 = y(2 + x) y =  f –1( x ) = 2x  1 2 x 2x 1 . Given that f : x  4 + 8x . find f –1. x  -2. 4. find f –1. Given that g : x  10 – 2x . 3.

4 x Functions 18 . find g–1 . Given that f(x) = 2x  5 . 6 7.MASTERY EXERCISES ON FINDING THE INVERSE OF A FUNCTION 1. Given that f : x  6x . Given that f : x  5 + 2x . find g–1 (x). Given that g : x  3 – 3 x . 4. find g –1 . Given that g : x  3 – 1 x . Given that g : x  3 – x . find f –1 (x). 5. Given that f : x  10 – 8x . 8. find g–1 (x). Given that f(x) = x2 . find f –1(x). 4x  2 10. 4 9. find f –1 . find f –1 . Given that g(x) = 2x . 2 3. find f –1 .15 . Given that g(x) = 3x  2 . 4 6. find g–1 . 2.

Given that g : x  5 + 2x . Given that g : x  7 – x . Given that g : x  g–1(4). Given that f : x  f –1 ( -1 ). find the value of f –1(-5). 6. Given that f : x  x + 2. 1 – x . find the value of g–1(2). 8. 7. 4 . then use Method 2 ) EXERCISES 1. find the value of f –1 (10). find the value of x 3 10. find the value of g–1(2). find the value of 2 9. 2 x Functions 19 . Given that f : x  7 – 3x . find the value of f –1(7). 3. 2. Given that g : x  7 – x . METHOD 1 [ Finding f –1 first ] f(x) = 2x + 1 f(y) = 2y + 1 f –1(2y + 1) = y f –1(x) = y METHOD 2 [ Without finding f –1(x) ] f(x) = 2x + 1 Let when x = 2y + 1 x – 1 = 2y y = f (x) = f –1(7) = = –1 f –1(7) = k f(k) = 7 2k + 1 = 7 2k = 6 k = 3  f –1(7) = 3 x 1 2 x 1 2 7 1 2 3 ( If you are not asked to find f –1( x ) but only want to have the value of f –1( a ). 5. find the value of f –1(-2). find the value of f –1(3). Given that f : x  4 + 6x . 4. find the value of g–1 (5).FINDING THE VALUE OF f–1 (a) WHEN GIVEN f(x) Example : Given that f : x  2x + 1. Diberi g : x  3 . cari nilai g-1(-1). Given that f : x  3x -2.

Finding the Other Related Component Function when given a Composite Function and One of its Component Function TYPE 1 ( Easier Type ) Given the functions f and fg. find the function g . find the function f. OR Given the functions g and fg . g(x) = 5x 2. find the function f . Given the functions f : x  2 x  2 and g f : x   5  6 x . Answer : Answer : Functions 20 . find the function g . Given the functions f : x  2 x  3 and fg : x  6 x  1 . Given the functions f : x  2 x  2 and fg : x  4  6 x .2 = 5x + 25 – 25  EXERCISES 1. 2. OR Given the functions g and gf. Given the functions f : x  2 x  5 and g f : x  10 x  25 . find the function g . EXAMPLE : 1. Answer : f(x) = 2x + 3 fg(x) = 6x – 1 Answer : f(x) = 2x – 5 gf(x) = 10x – 25 Find g(x) from fg(x) = 6x – 1 f [g(x)] = 6x – 1 Find g(x) from gf(x) = 10x – 25 g [ f(x) ] = 10x – 25 g ( 2x – 5) = 10x – 25 g ( 2y – 5) = 10y – 25 g(x) = 10y – 25 when x = 2y – 5 x + 5 = 2y y= So : g(x) = 10 ( x5 ) – 25 2 x5 2 2 g(x) + 3 = 6x – 1 2 g(x)  g(x) = 6x – 4 = 3x . find the function g. find the function g . TYPE 2 ( More Challenging Type ) Given the functions f and gf . find the function g .

find the function g. Given the functions f : x  2x + 7 and fg : x  7 – 4x . Answer : 2. Given the functions h : x  3x + 1 and hf : x 7 – 9x2 . Answer : Functions 21 . Answer : 7.REINFORCEMENT EXERCISES on finding Component Function from Composite Function ( TYPE 1 ) 1. find the function g . Answer : 10. find the function g. Answer : 5. find the function f .1 and gf : x 6x + 7 . Given the functions g : x  2x . Given the functions p : x  2x and pq : x 4 – 2x . Given the functions f : x  2x – 3 and fg : x 2x + 3. Given the functions g: x  x + 3 and gf : x  2x . Given the functions h : x  1 – x and hg : x  1 – 3x2. Given the functions f : x  2 – x and fg : x 2 – 2x . find the function f . find the function q. find the function f . find the function g . Answer : 3. find the function g . Answer : 6. find the function f . Answer : 9. Given the functions f : x  3x + 4 and fg : x 6x + 1.. Answer : 8. Given the functions g : x  2 + 4x and gf : x  6 + 4x2. Answer : 4.

Given the functions g : x  2x .1 and fg : x  6x + 1 . Answer : 7. Given the functions f : x  3x + 4 and gf : x  6x + 7..3x . Answer : 5.. Answer : 6. Given the functions f : x  3x and gf : x  1 . find the function f. Answer : Functions 22 .. Given the functions g : x  2x and fg : x 2 – 2x . find the function g.REINFORCEMENT EXERCISES on finding Component Function from Composite Function ( TYPE 2 ) 1.. Given the functions f : x  2 – x and gf : x 4 – 2x . Answer : 2. Given the functions f : x  2x . Answer : 4. Answer : 8. Given the functions f : x  2 + 4x and gf : x 5 + 16x + 16x2. find the function g.. find the function f. find the function g.3 and gf: x 2x . Given the functions g: x  x + 3 and fg : x  2x + 3 . find the function f. find the function g. Answer : 3. find the function g.

the object of 4. (b) hf (x) . (1. find (a) f –1( –1) . the type of relation Ans: Ans: Ans: Ans: Ans: Ans: The above diagram shows the relation between set A and set B State (a) the images of b. 2. (c) f h(x). 10} 2. 6. 4). the codomain. the domain. (a) f –1 (5) . (c) f2 (x) . 6). (2. 5. Given the functions f : x  2 x  1 and h : x  x  x  2 . (2. find 2 h : x  2  x 2 . Functions 23 . find (a) g –1 (3) . 4. Base on the information above. Ans: (c) the domain. a relation from P into Q is defined by the set of ordered pairs { (1. Ans: (b) the objects of p. 8. Given the functions g : x  4 x  1 and 3. 6). Ans: (f) the type of relation Ans: 4. Given the function f : x  2  3 x and 6. 8) }. State (a) (b) (c) (d) (e) (f) a• b• c• A •p •q •r •s B the images of 1. Ans: (e) the range. (b) gf (x) . the range. (a) f –1 (3) . P = { 1.QUESTIONS BASED ON SPM FORMAT 1. Given the functions f : x  2 x  1 and g : x  x  3 . (b) hg (x) . 3} 2} Q = {2. Ans: (d) the codomain. find 2 h : x  x 2  3 . (b) hf (x) .

find the values of a and b . n = 9. g : x  a  bx 2 and 1 4 ] [ a = 8 . 1 : x  nx  3 . Given the inverse function f 1 ( x)  . Given that f : x  2 x  1 . find find the values of m and n. Given that g(x) = mx + n and g (x) = 16x – 25 .m=4] 6 [a=2. [ m = 4 . m = –4 . [ m = –3 . 4 8.b=6] 2 11. Given that g : x  m  3 x and g 1 : x  2kx  find the values of m and k. b = –1 ] 10. Given that f : x  x  3 . 2x  3 12. Given that f : x  4 x  m and f find the values of m and n.7. g : x  4 x and fg : x  ax  b . n = 25 3 ] [ (a) 11 2 . n = –5 . [k= 1 . (b) the value of k if f –1 (2k) = –k – 3 . 2 (a) the value of f(4). 3 gf : x  6 x 2  36 x  56 . (b) k =  1 2 ] Functions 24 . 4 . find the values of a and b .

p  3x . where m is a constant. m=4 p=4 Functions 25 . P2. (b) f – 1 g(x) . (SPM 06. (c) h(x) such that hg(x) = 2x + 6 . Q2) Given the function f : x  3 x  2 and 2. Q2) mx Diagram 2 shows the function h : x  . where p is a constant. (c) h(x) such that hg(x) = 6x – 3 . x2 3 (b) x  15 10 (c) 10x – 4 (a) 4. –1 g:x x  2 . P1. find 5 (a) f (x) . Given the function f : x  2 x  1 and x g : x   1 . (b) f – 1 g(x) . (a) 3. x 1 2 (b) 1 1 x 6 2 (c) 18x + 9 (SPM 06. x2 x h mx x x g p  3x x2 8  1 2 7 5 Diagram 3 Find the value of p. find 3 (a) f –1 (x) . Diagram 2 Find the value of m. x x  0 . Diagram 3 shows the function g : x  x  2 .QUESTIONS BASED ON SPM FORMAT 1.